Missionaries and the Construction of Christian Homes: Examining the Formation of African Social Identities in Colonial Malawi - Tembo, Dorothy (International bulletin of mission research, 2022)
Christian missions were introduced in Africa to bring commerce and civilization. Nevertheless, the modernizing ambitions of missions and the colonial government had considerable social and moral consequences, which are observable in the construction of a Christian family. This article will show that missionaries created a social revolution by prohibiting polygamy, leading to wives being treated as widows. Besides, the article will show that the construction of femininity and masculinity in mission schools was based on European culture. Eventually, some roles that in traditional society were reserved for men were defined as feminine tasks.